Severity and duration of heat stress in calves and heifers in the main intensive dairy localities of the department of Lima, Peru - Ruiz G., Luis Felipe (2017)
The aim of this study was to determine the severity and duration of heat stress in dairy calves and heifers of the five main dairy localities in Lima, Peru (Végueta, Huacho, Huaral, Lurin, Cañete) during the period 2010-2013. The temperature-humidity index load (ITH load) and the duration of the heat stress per month and location were evaluated. In addition, the percentage of days in the year in which ITH load was greater than 0. The results showed that the ITH load was greater than zero in all months of the year for heifers. Also, February was the month where heat stress occurred with greater severity and duration, both in heifers and in calves and Cañete was the locality with the highest ITH overload for calves and heifers. Regarding the duration of heat stress, heifers and calves spent about 10 and 5 hours a day, respectively, exposed to caloric stress during the summer months. Heifers in Végueta and Cañete spent 86 and 83% of days of the year with heat stress, respectively, while calves in Cañete spent 47% of the days in heat stress. It is concluded that heat stress in heifers in the localities of Cañete and Végueta, as compared with the other localities, occurred with greater severity and duration, whereas it only occurs in Cañete for calves.